THE IMPACT OF RATIO ANALYSIS ON THE EVALUATION AND MANAGEMENT OF LIQUIDITY IN AGRO-PROCESSING COMPANIES - Miroslav Čavlin; Mirko Pešić; Sanja Pešić (Ekonomika Poljoprivrede (1979))
Liquidity is a fundamental element of business partnerships, directly influencing the establishment or loss of trust, with emphasis on the dynamics financial interactions. Тhe assessment of liquidity in financial analysis requires the use of predefined metrics or analytical guiding star. The aim of this research is to investigate the contribution of ratio analysis on the valuation and management of liquidity in agro-processing enterprises. The research employs annual financial reports of agroprocessing companies from 2016 to 2023, utilizing regression analysis to identify critical challenges in liquidity management. The findings show that there is a positive correlation between the selected metrics of the static and dynamic basis of liquidity, and their negative correlation with the indebtedness indicator on the example of the agro-processing industry of Serbia. The contribution of this study is that its results can be used in the preparation and implementation of effective liquidity strategies in agroprocessing companies.